Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/6608870
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Characteristics, Prognostic Determinants and the Outcome of Patients Diagnosed with Colorectal Adenocarcinoma at the University Teaching Hospital of Kigali

Abstract: Worldwide, colorectal cancer (CRC) is the second most diagnosed cancer in female and the third in men, arising from the epithelium of the colorectum. It is known that colorectal cancer is common in developed countries than in developing countries which may be due to inaccurate data on the existence of the disease in that region combined with embracing western lifestyle expressed by the current trend of changes in cultural, social, and lifestyle practices playing a major part in the etiology of CRC. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 21 publications
5
4
1
Order By: Relevance
“…In contrast to global data where CRC is reported to be more common in males than in females [9], in this study, we found that CRC was more common in females than in males (i.e., 63.0% versus 37.0%). Our findings also report a higher rate of female incidence than the 52.5% reported by Uwamariya et al [18] and the 52.2% reported by Fadelu et al [19].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In contrast to global data where CRC is reported to be more common in males than in females [9], in this study, we found that CRC was more common in females than in males (i.e., 63.0% versus 37.0%). Our findings also report a higher rate of female incidence than the 52.5% reported by Uwamariya et al [18] and the 52.2% reported by Fadelu et al [19].…”
Section: Discussionsupporting
confidence: 71%
“…They, therefore, immediately undergo resection to relieve the obstruction without undergoing colonoscopy. This speculation may be supported by the fact that Uwamariya et al [18] found that rectal cancer accounted for 40% of all CRC cases in a study conducted at the same institution as ours that used both biopsy and resection specimens.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Among 74 patients, we found that the mean age at diagnosis was 54.6 years with a wide age range between 22 and 81. This finding is similar to previous findings at the BCCOE and Kigali University Teaching Hospital (KUTH) with reported mean age at presentation of 52.5 and 54.3 years, respectively [ 24 , 25 ]. The mean age of males at diagnosis was 56.6 years and the mean age of females at diagnosis was 51.4 years.…”
Section: Discussionsupporting
confidence: 91%